Faktor Penghambat Peranan Stakeholders dalam Pemberdayaan Pelaku Industri Kecil dan Menengah Perikanan di Kabupaten Pesisir Selatan - Prayoga Ramadhina, Ramona; Eriyanti, Fitri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to identify factors that hinder the role of stakeholders in empowering fisheries' small and medium industry (SMI) actors in Pesisir Selatan Regency. This research used a qualitative method with a descriptive approach conducted in Koto XI Tarusan Sub-district, Pesisir Selatan Regency, West Sumatra Province. Data were collected through interviews, observations, and documentation studies, and data validity was checked using source triangulation techniques. The results showed that some of the factors that hinder the empowerment of fisheries SMEs by stakeholders include budget constraints, lack of human resources in the Trade and Transmigration Office as one of the main stakeholders, time constraints, low motivation of fisheries SMEs to participate in empowerment programs, and difficulties for SMEs in meeting the standards or product legality requirements of Budiman Swalayan.